The Potential Role of Artificial Intelligence in Capturing Census Data - Mushonga, Warren (The IIE, 2020)
“For too long, African leaders have undermined the growth of Africa. They lost the plot of measurement because they could not count numbers” (Lehohla, 2011). Census plays a critical role in the development of a country. The government needs to use census data for planning purposes for example to provide grant payments and service delivery. Since the world is gearing up for the Fourth Industrial Revolution, it is crucial for Statistics South Africa to enter into a transitioning phase of using artificial intelligence in capturing census data. The focus of this research is that the traditional census methods used by Statistics South Africa to capture census data have resulted in undercounts. This research used an interpretivist, qualitative approach to promote a deeper understanding on the potential role of artificial intelligence in capturing census data. This research used in-depth semi structured interviews as a data collection method, which allowed the researcher to generate the research findings. The most significant finding of this research is that artificial intelligence has the potential to produce accurate census data compared to traditional census methods. Lastly, this research can enlighten readers on the importance of accurate census data and the use of artificial intelligence.
Keywords: Census data; Artificial intelligence (AI); Fourth Industrial Revolution (4IR)